Exploring Perceptions Of Productivity and Well-Being Among High-Demand Professionals - Paltarak, Mikita; Ryška, Tomáš, 1976-; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis arises from a growing need to address a critical gap in both academic research and professional practice: the lack of a structured understanding of individual productivity strategies in high-demand work environments, such as consulting, investment banking, and technology. While existing literature has focused largely on organizational-level interventions, few studies have explored the personal tools and cognitive habits that enable professionals to sustain their performance over time—especially in roles characterized by long hours, high expectations, and psychological strain. To address this gap, the study first introduces a theory-driven framework that divides personal productivity into three core domains: Effectiveness (task prioritization and decision-making), Efficiency (time management and process optimization), and Occupancy (attention, energy, and cognitive wellness). The framework is developed through an extensive literature review and validated through a two-phase empirical study. A quantitative survey of 105 professionals across high-pressure industries tests whether the consistent application of strategies across these domains correlates with greater productivity, satisfaction, and lower burnout—revealing strong support for this multidimensional model. A complementary qualitative phase deepens this insight, revealing that beyond strategy, mindset plays a pivotal role in sustaining high performance. Interviews uncovered practices such as mental reframing, self-motivation rituals, and value alignment, prompting an extension of the original framework to include Mindset as a fourth pillar of personal productivity. Together, the findings contribute a robust, validated model for understanding how individuals perceive productivity in high-demand jobs—offering both theoretical advancement and practical guidance for those who want to feel more productive. Literature Used: Harung, H. S. (1998).
Reflections: Improved time management through human development: achieving most with least expenditure of time. Journal of Managerial Psychology, 13(5/6), 406–428. Hewlett, S. A., & Luce, C. B. (2006). Extreme jobs: the dangerous allure of the 70-hour workweek. Harvard Business Review, 84(12), 49–59. Aeon, B., Faber, A., & Panaccio, A. (2021). Does time management work? A meta-analysis. PLoS ONE, 16(1), e0245066. Allen, D. (2015). Getting Things Done: The Art of Stress-Free Productivity. Penguin. Claessens, B. J., Van Eerde, W., Rutte, C. G., & Roe, R. A. (2007). A review of the time management literature. Personnel Review, 36(2), 255–276. Davenport, T. H., & Beck, J. C. (2001). The attention economy. Ubiquity, May 2001, Article Banbury, S. P., & Berry, D. C. (2005). Office noise and employee concentration: Identifying causes of disruption and potential improvements. Ergonomics, 48(1), 25–37. Choe, E. K., Lee, N. B., Lee, B., Pratt, W., & Kientz, J. A. (2015). Understanding Quantified- Selfers’ practices in collecting and exploring personal data. Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems, 1021–1030. Lambusch, F., Fellmann, M., Poppe, M., Weigelt, O., & Hein, S. (2020). Personal productivity management in the digital age: Measures from research and use of conventional tools. In Wirtschaftsinformatik (Zentrale Tracks) (pp. 632–647). Kim, Y. H., Choe, E. K., Lee, B., & Seo, J. (2019). Understanding personal productivity: How knowledge workers define, evaluate, and reflect on their productivity. In Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems (pp. 1–12).
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses